The wealthy barber : everyoneʼs commonsense guide to becoming financially independent - Chilton, David ([Rocklin, Calif.] : Prima Pub., 1998)
The book simplifies the complex puzzles of personal finance and helps you achieve financial independence.
rua 28/08/13
Loans
Keywords: Finance, Personal; Wealthy barber; Financial independence